Integrative multi-omics analysis of the microbiome and metabolome in bronchoalveolar lavage fluid from patients with early-stage lung cancer - Jiajun Xie; Nengyang Zhu; Weiguo Xu (Frontiers in Cellular and Infection Microbiology)
Lung cancer is a significant health concern that poses a considerable threat to human health and quality of life. In order to enhance the prognosis of patients with lung cancer, we conducted a combined analysis of 16S rDNA gene sequencing of alveolar lavage fluid and LC-MS metabolomics research, with the objective of identifying biomarkers in patients with early-stage lung cancer presenting as SPN. A comparison of the benign nodule group and the early-stage lung cancer patients revealed that the phylum-level Bacteroidetes and the genus-level Chryseobacterium and Delftia were more abundant in the latter group. Additionally, the Fusobacteriales might serve as a predictive marker for the diagnosis of early-stage lung cancer. In the context of metabolomics, the early-stage lung cancer was found to be characterised by elevated levels of specific metabolites, including Alternariol, dTMP, Oxymatrine, Gedunin, PC 36:4. Conversely, reductions in other metabolites, such as LPC O-24:0, PC 18:2_18:3, PC 19:2_19:2, Cholecalciferol and T-2 Triol, were also observed. Correlation analyses demonstrated that alveolar lavage microorganisms were closely associated with differential metabolites. Specifically, reductions in Cholecalciferol were associated with a variety of high-abundance flora and involved in vitamin digestion and absorption pathways. Furthermore, reductions in cholecalciferol may serve as a robust predictor of early-stage lung cancer. These findings provide new predictive biomarkers for early-stage lung cancer manifested by SPN, which is clinically important and requires further study of the potential mechanisms of action and function of the targets.